The Influence Of Personal Selling And Publicity On Increasing Sales Volume - Prabawati, Achadyah; Yulindasari, Vivi (Jurnal Penelitian IPTEKS, 2024)
Increase in sales volume is the amount of sales achieved within a company in a certain time period. Factors that influence increasing sales volume are personal selling and publicity. The aim of this research is to determine the effect of personal selling and publicity on increasing sales volume both directly and indirectly (at CV Raja Tani Makmur). This research is quantitative research with associative research type. The sample in this study consisted of 30 respondents. Data collection methods use observation, questionnaires and interviews. The analysis method is multiple linear regression assisted by IBM 24 software. The research results show that. 1. Personal selling and publicity have a significant influence on increasing sales volume. 2 Personal selling has a positive and significant effect on increasing sales volume. 3. Publicity has a positive and significant effect on increasing sales volume